Pengaruh Lingkungan Kerja dan Stres Kerja terhadap Produktivitas Kerja dengan Variabel Moderating Kepuasan Kerja - Istiqomah, Hindun; Suji’ah, Uju (CV. Kurnia Grup, 2024)
This research aims to determine the influence of the work environment and work stress on work productivity with the moderating variable job satisfaction. The total sample was 81 employees with a saturated sampling technique. The data collection method uses a questionnaire. Data testing uses validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests, coefficient of determination tests, and absolute difference tests. The research results show that 1) the work environment has a significant influence on work productivity. 2) work stress has a significant influence on work productivity. 3) the work environment and work stress have a significant influence on work productivity. 4) job satisfaction does not moderate the influence of the work environment on work productivity. 5) job satisfaction does not moderate the influence of work stress on work productivity. 6) the results of the coefficient of determination test (R2) of the work environment and work stress have an influence on work productivity of 97. 4 percent, while the remaining 2. 6 percent is influenced by other factors not examined in this research.